Unveiling Cultural Insights in Pramoedya Ananta Toer’s ‘Rumah Kaca': A Sociopragmatic Analysis - Yunita Warinangin; Rosmawati (JOURNAL OF SOCIETY INNOVATION AND DEVELOPMENT, 2025)
Background of the problem: Literature not only reflects human beauty and creativity but is also a forum for conveying deep messages about life, philosophy and culture. Purpose: This research aims to analyze the expression of cultural values in the story construction of the novel "Rumah Kaca" by Pramoedya Ananta Toer, with a focus on traditional Javanese cultural values and modern European cultural values reflected in the narrative. Method: A library research approach and qualitative descriptive methods. Secondary data was obtained from digital libraries, documents and scientific journals. Data analysis was carried out through reduction, narrative presentation and drawing conclusions. Result: The novel "Rumah Kaca" is a medium that depicts the combination and conflict between traditional Javanese cultural values and modern European cultural values. Sociopragmatic analysis reveals how the characters in the novel reflect the different views and values that characterized society's life at that time. Implication: This study enhances the understanding of how traditional Javanese and modern European cultural values coexist and conflict within Indonesian literature. It promotes cultural awareness and appreciation among readers, highlighting the richness and diversity of cultural narratives.